Plant invasions in Italy: An integrative approach using the European LifeWatch infrastructure database. (August 2018) - Malavasi, Marco; Acosta, Alicia Teresa Rosario; Carranza, Maria Laura; Bartolozzi, Luca; Basset, Alberto; Bassignana, Mauro; Campanaro, Alessandro; Canullo, Roberto; Carruggio, Francesca; Cavallaro, Viviana; Cianferoni, Fabio; Cindolo, Claudia; et al.
Highlights: Analysis of plant invasions in Italy across different terrestrial sites and habitats. Invasion is driven by a combination of propagule pressure, abiotic and biotic factors. The accessibility time from major towns is a sound predictor of invasion risk. Abiotic filter and biotic competition pose a limit to the settlement of alien species. LifeWatch successfully supported the macro-ecological assessment of invasion risk. Abstract: By using the LifeWatch database – a European e-science infrastructure on native and alien plant occurrence collected from a wide set of Italian terrestrial sites – we estimated the occurrence of alien species in a cross-habitat framework in relation to propagule pressure (P), abiotic (A) and biotic (B) conditions. The research represents an example of macro-ecological assessment of invasion risk at national scale claimed by the recent European regulation (EU 1143/2014) on invasive alien species. Based on a large vegetation dataset, we estimated alien and native species richness across a set of 19 Italian terrestrial sites. By using a Generalized Linear Mixed Model, we investigated the relationship between the proportion of alien occurrence across sites and habitat types (EUNIS) at family level with PAB putative drivers derived from LifeWatch and other open access geographic databases. Our results support the full model as the best-fitting option, highlighting that plant invasion in the Italian terrestrial ecosystems is a function of the combination of PAB conditions. In the first step of the invasion process, the accessibility time from towns plays a major role. By contrast, the abiotic filter imposed by environmental condition (high temperatures and low precipitations) as well the competition with the native community (high species richness) may pose a limit to the settlement and spread of alien species. Because of the high availability of similar data on PAB conditions worldwide, this study represents an effective and easy tool to design appropriate biodiversity conservation policies focused on the prevention of alien spread.